Electrochemical synthesis of hydrogen with depolarization of the anodic process - Tulskiy, Gennadiy; Tulskaya, A. G.; Skatkov, L. I.; Gomozov, V. P.; Deribo, S. G. (My University, 2016)
A new active composite coating for graphite gas diffusion electrode for hybrid sulfur cycle was proposed. The kinetics of oxidation of SO₂ were studied on porous graphite anodes with different catalytic coatings. It was shown that the most efficient composite coating is based on activated carbon and platinum supported on graphite gas diffusion substrate. The voltage drop in the laboratory electrochemical cell was 1.3 V at a current density of 1000 A·m⁻². This corresponds to a specific consumption of 3.1 kWh electric energy per 1 m³ of hydrogen.
Keywords: active composite coatings; hydrogen; depolarization